VD_FINDINFO Jug / 2009 / 46 vom 26. August 2009 - VD Tribunal cantonal (2009)
DROIT AU GAIN, LIQUIDATION DU RÉGIME MATRIMONIAL, RÉCOMPENSERÉGIME MATRIMONIAL | 206 CC, 207 CC, 209 CC, 212 CC, 215 al. 1 CC, 28 LDFR, 29 LDFR, 30 LDFR, 31 al. 1 LDFR, 31 al. 4 LDFR